Analysis of microbiota in stable patients with chronic obstructive pulmonary disease. Issue 5 (6th April 2015) - Aguirre, Estefania; Galiana, Antonio; Mira, Alejandro; Guardiola, Ramón; Sánchez‐Guillén, Laura; Garcia‐Pachon, Eduardo; Santibañez, Miguel; Royo, Gloria; Rodríguez, Juan Carlos
Abstract : To identify the bacterial diversity (microbiota) in expectorated sputum, a pyrosequencing method that investigates complex microbial communities of expectorated sputum was done in 19 stable chronic obstructive pulmonary disease patients (mean (SD) FEV1: 47 (18%) of predicted value). Using conventional culture, 3 phyla and 20 bacterial genera were identified, whereas the pyrosequencing approach detected 9 phyla and 43 genera (p < 0.001). In sputum the prevalent genera with pyrosequencing approach were Streptococcus, Actinomyces, Neisseria, Haemophilus, Rothia, Fusobacterium, Gemella, Granulicatella, Porphyromonas, Prevotella and Veillonella . Enterobacteriaceae, detected frequently in conventional culture, were not significantly detected with pyrosequencing methods. In addition, we found that important pathogens such as Haemophilus and Moraxella were detected more frequently with the new genetic procedures. The presence of Enterobacteriaceae is probably overestimated with conventional culture, whereas other difficult cultivable pathogens are underestimated. These studies open a new perspective for evaluating the role of bacterial colonization in chronic obstructive pulmonary disease pathogenesis and progression.